Структурная схема подсистемы анализа гемореологических показателей - Максюта, Наталия Валерьевна; Поворознюк, Анатолий Иванович; Будянская, Э. Н. (НТУ "ХПИ", 2006)
В статті розглянуті засоби дослідження реологічних властивостей крові та їх вплив на стан здоров’я організму людини. Розроблено структурну схему підсистеми аналізу гемореологічних показників, яка в змозі забезпечити синтез якісного комп’ютерного діагнозу за мінімальні витрати часу на обслідування пацієнта з урахуванням наявності необхідних приладів вимірювання та класів захворювань.

In article ways of research reology properties of blood and their influence on a state of health of an organism of the person are considered. The block diagram of process of statement of the diagnosis is offered in view of intellectual computer system of medical diagnostics. The block diagram of a subsystem of the analysis reology parameters which provides synthesis of the qualitative computer diagnosis in view of an available set of devices of measurement and classes of diseases in the time expenses reduced up to a minimum necessary on inspection of the patient is developed.
Keywords: свойства крови; вязкость плазмы; эритроциты; тромбоциты; вискозиметр; гематологический анализатор